2014
DOI: 10.2215/cjn.11971113
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiling and Incident CKD among African Americans

Abstract: Background and objectives Novel biomarkers that more accurately reflect kidney function and predict future CKD are needed. The human metabolome is the product of multiple physiologic or pathophysiologic processes and may provide novel insight into disease etiology and progression. This study investigated whether estimated kidney function would be associated with multiple metabolites and whether selected metabolomic factors would be independent risk factors for incident CKD.Design, setting, participants, & meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
79
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 45 publications
7
79
0
2
Order By: Relevance
“…In this study, the authors first examined the cross-sectional association of serum metabolite levels with eGFR calculated using the CKD-EPI study equation (eGFR CKD-EPI ). Consistent with several prior reports (9-12), Yu et al found that the levels of many metabolites are higher among individuals with lower eGFR (8). Extending these cross-sectional observations, Yu et al linked metabolite profiles at the beginning of follow-up to the future occurrence of CKD, defined as an eGFR CKD-EPI ,60 ml/min per 1.73 m 2 and ,75% of baseline, or a CKD-related hospitalization or death during a median follow-up of 19.6 years.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the authors first examined the cross-sectional association of serum metabolite levels with eGFR calculated using the CKD-EPI study equation (eGFR CKD-EPI ). Consistent with several prior reports (9-12), Yu et al found that the levels of many metabolites are higher among individuals with lower eGFR (8). Extending these cross-sectional observations, Yu et al linked metabolite profiles at the beginning of follow-up to the future occurrence of CKD, defined as an eGFR CKD-EPI ,60 ml/min per 1.73 m 2 and ,75% of baseline, or a CKD-related hospitalization or death during a median follow-up of 19.6 years.…”
supporting
confidence: 89%
“…Extending these cross-sectional observations, Yu et al linked metabolite profiles at the beginning of follow-up to the future occurrence of CKD, defined as an eGFR CKD-EPI ,60 ml/min per 1.73 m 2 and ,75% of baseline, or a CKD-related hospitalization or death during a median follow-up of 19.6 years. Using Cox proportional hazards models to analyze the 1921 study participants (204 of whom developed CKD), the authors highlight 5-oxoproline (hazard ratio , 0.70 per 11 SD; P,0.001; 95% CI, 0.60 to 0.82; [8]) and 1,5-anhydroglucitol (hazard ratio, 0.68 per 11 SD; P,0.001; 95% CI, 0.58 to 0.80; [8]) as significant markers whose higher levels were associated with a decreased risk of future CKD, after adjusting for baseline eGFR, age, sex, systolic BP, antihypertensive medication use, diabetes status, smoking status, coronary heart disease, as well as HDL and LDL cholesterol.The explanation for why higher levels of these markers were associated with lower disease risk is unclear. The authors speculate that elevated 5-oxoproline levels may be salutary by contributing to the biosynthesis of glutathione, an antioxidant that could attenuate the oxidative…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As alterações incluem desequilíbrios ácido-base, homeostase (Goek et al, 2013;Rhee et al, 2013;Yu et al, 2014).…”
Section: Metabolismo E Doença Renal Crônicaunclassified
“…Análises dos perfis metabólicos plasmáticos de pacientes renais crônicos identificaram modificações em diversos metabólitos, entre eles: moléculas relacionadas ao metabolismo do triptofano, como indoxil sulfato, ácido quinurênico, quinurenina e outros como intermediários do ciclo de Krebs, aconitato e isocitrato (Goek et al, 2013;Rhee et al, 2013;Yu et al, 2014).…”
Section: Metabolismo E Doença Renal Crônicaunclassified